PENANAMAN NILAI-NILAI RELIGIUS DALAM TPA KB-TK YAA BUNAYYA KUDUS - Shafaa Salsabilla Duratul Azis; Moh Yasir Alimi (Jurnal Ilmiah Sosiologi Agama (JISA), 2025)
The cultivation of religious values in early childhood is a crucial aspect in shaping children's spiritual, moral, and social character from an early age. This study aims to examine the process of instilling religious values at TPA KB-TK Yaa Bunayya Kudus, an early childhood education institution with a religious foundation. The focus of the study includes the types of values being taught, the stages of the value cultivation process, and the factors influencing its success. This research employs a descriptive qualitative approach with data collection techniques consisting of observation and interviews. The results indicate that the religious empathy, discipline, and responsibility. The cultivation process is carried out through three main stages, namely introduction, habituation, and reinforcement, all of which are adapted to the developmental characteristics of early childhood. The success of this process is supported by several factors, such as daily habituation, the role modeling provided by the teachers (ustadzah), and collaboration programs with parents. Nevertheless, several challenges were identified during the implementation, including variations in children's developmental stages, inconsistencies between parenting at home and at school, as well as the influence of the child's social environment. The findings were analyzed using Lawrence Kohlberg's moral development theory, which revealed that the applied approach aligns with the moral developmental stages of early childhood. This research contributes to enriching applicable startegies for cultivating religious character in early childhood education institutions